THE FACTORS WHICH ARE RELATED TO LEVEL ACCREDITATION IN THE PUBLIC HEALTH CENTER IN KONAWE DISTRICT: LEVEL ACCREDITATION IN THE PUBLIC HEALTH - Isjan Harisal Liambo; Tasnim Tasnim; Jasmurni Munir (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2022)
Background: Based on a preliminary survey conducted at a public and basic accredited health center by interviewing several staff at the health services , they said that the accredited Public health center had human resources in terms of quality and quantity, inadequate facilities and infrastructure. Also, administrative services  was under standard operating procedures and it has not been carried out optimally. The quality of service has not met the standards as a service facility at the first level. Methods: This study is an observational study which used a cross sectional approach. The sample in this study were 139 health workers. The analysis used  chi square. Result: There is a significant positive relationship between resources with the level of Public health center accreditation ( p-value= 0.000<0.05). There is a significant positive relationship between infrastructure and the level of accreditation ( p-value= 0.000<0.05). There is a significant positive relationship between service quality and accreditation level ( p-value= 0.005<0.05). Conclusion: There is the relationship between resources, infrastructure, service quality and the level of Public health center accreditation.